2015
DOI: 10.1002/marc.201500060
|View full text |Cite
|
Sign up to set email alerts
|

Aminobisphosphonate Polymers via RAFT and a Multicomponent Kabachnik–Fields Reaction

Abstract: Polyacrylamides containing pendant aminobisphosphonate groups are synthesized via reversible addition-fragmentation chain transfer (RAFT) polymerization and a multicomponent postpolymerization functionalization reaction. A Moedritzer-Irani reaction installs the phosphonic acid groups on well-defined, RAFT-generated polymers bearing a pendant amine. An alternate route to the same materials is developed utilizing a three-component Kabachnik-Fields reaction and subsequent dealkylation. Kinetics of the RAFT polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…31 ). However, the conditions of the Moedritzer–Irani reaction induced the hydrolysis of the polymers side chains [ 226 ].…”
Section: Reviewmentioning
confidence: 99%
“…31 ). However, the conditions of the Moedritzer–Irani reaction induced the hydrolysis of the polymers side chains [ 226 ].…”
Section: Reviewmentioning
confidence: 99%
“…Commonly used heavy metals, such as plutonium and uranium, exhibit both chemical and radiological toxicities. To address these concerns, bisphosphonate‐ and aminobisphosphonate‐based polymers have been investigated as multidentate materials to chelate heavy metals . Lahrouch et al recently demonstrated the affinity of polyethyleneimine methylphosphonate (PEI‐MP) (Fig.…”
Section: Polymer Chelation Therapymentioning
confidence: 99%
“…Examples of such MCRs include the Passerini, Ugi, Biginelli, Hantzsch, Kabachnik–Fields (KF), and Mannich reactions. [ 15–32 ] MCRs are suitable for the preparation of polymer antioxidants for several reasons. Some antioxidative groups such as phenol are compatible with many MCRs and can be easily introduced into polymer chains without losing their antioxidative ability.…”
Section: Introductionmentioning
confidence: 99%
“…[ 37–40 ] However, the KF reaction has been used only recently in polymer chemistry. [ 26,28,29,41–45 ] Some new polymers have been prepared via the KF reaction and used as flame‐resistant and antibacterial materials. [ 43–45 ] However, the preparation of antioxidant polymers via the KF reaction has not been reported.…”
Section: Introductionmentioning
confidence: 99%